UPAYA GURU BK DALAM MENGATASI PESERTA DIDIK YANG UNDER ACHIEVER - Defriani, Gusri - (Bimbingan dan Konseling, 2014)
This research was based of counselor still not make an effort to help a students who haveunder achiever. This study aimed to describe: 1) Efforts counselor in understanding students underachiever based on internal factors, 2) Efforts counselor in understanding students under achieverbased on external factors, 3) Efforts counselor in addressing student under-achiever. This researchwas conducted with a qualitative descriptive approach. As an informant researcher take 3 as keyinforman and aditied informant 2 other. To gathering the data research using interview and thedata analyze with data reduction, data presentation and conclusion. The purposes study of thisresearch using: 1) Efforts counselor understanding students under achiever by internal factorsalready done but not maximized. 2) Efforts counselor in understanding students under achiever byexternal factors has been carried out with the maximum. 3) Efforts counselor in addressing studentunder-achiever already done but not maximized.